DYNAMIC MODELLING OF A FLEXIBLE LINK MANIPULATOR ROBOT USING AMM - Moh. Khairudin Moh. Khairudin (Universitas Ahmad Dahlan, 2008)
This paper presents modeling of a flexible link manipulator using Lagrangian technique in conjunction with the assumed mode method (AMM). The links are modeled as Euler-Bernoulli beams satisfying proper mass boundary conditions. A payload is added to the tip of the outer link, while hub inertias are included at the actuator joints. The Lagrangian approach is used to derive the dynamic model of the structure. In this research, the dynamic model of a flexible link manipulator verified using Matlab/Simulink simulation. The model formulation proposed in this work is complete in the sense that it considers the effects of payload and damping structural of the link. The emphasis has been set on obtaining accurate equations of motion that display the most relevant aspects of the coupling between rigid and flexible dynamics.